PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA BERBASIS SiPanTer - Syamsul Bahri; Muhammad Lintang Cahyo Buono (Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to develop a digital learning device for moodle-based physics subjects using the SiPanTer LMS, which is feasible to use. The type of research used is development research using a 4D model in product development which includes four stages, namely the define, design, development, and dissemination phases. The limited and broad trial subjects consisted of 3 and 17 teachers, prospective physics teachers from 10 high schools in district Merauke, and a physics education graduate from Musamus University who has not served at school. The research instrument used is an expert validation instrument to assess the feasibility of the product and a questionnaire instrument to see the teacher's response to the product developed. The data analysis technique used is descriptive data analysis. The results showed that the SiPanTer-based physics learning device was feasible to use